2021
DOI: 10.3389/fonc.2021.698113
|View full text |Cite
|
Sign up to set email alerts
|

Are People With Blood Group O More Susceptible to Nasopharyngeal Carcinoma and Have Worse Survival Rates? A Systematic Review and Meta-Analysis

Abstract: ObjectiveNasopharyngeal carcinoma (NPC) is a common malignant tumour in Southeast Asia, especially in southern China. ABO blood groups have been proven to play an important role in many cancers. However, it is still controversial whether the ABO blood group has a definite relationship to susceptibility to NPC and the prognosis of NPC patients. This meta-analysis was performed to elucidate the correlation between ABO blood group and NPC to provide more data for clinical practice.MethodsA systematic search was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…At present, it is considered that its pathogenesis is closely related to EB virus infection, chemical carcinogens, and genetic susceptibility genes [ 2 , 3 ]. Radiotherapy is still the main treatment for NPC, but the local recurrence and distant metastasis easily occur after radiotherapy, which limits its ability to further improve the survival rate of patients [ 4 ]. The research on the related pathogenesis and metastasis mechanism of NPC is beneficial to the discovery of specific diagnostic indicators and gene therapy targets for NPC and has far-reaching significance.…”
Section: Introductionmentioning
confidence: 99%
“…At present, it is considered that its pathogenesis is closely related to EB virus infection, chemical carcinogens, and genetic susceptibility genes [ 2 , 3 ]. Radiotherapy is still the main treatment for NPC, but the local recurrence and distant metastasis easily occur after radiotherapy, which limits its ability to further improve the survival rate of patients [ 4 ]. The research on the related pathogenesis and metastasis mechanism of NPC is beneficial to the discovery of specific diagnostic indicators and gene therapy targets for NPC and has far-reaching significance.…”
Section: Introductionmentioning
confidence: 99%
“…Through extensive search, we collected quantitative evidence on ABO blood group associated with cancers and conducted meta‐analyses for 20 cancers totaling 20 million participants including 231 737 patients with eligible data across multiple comparison models. With an enlarged number of participants, our study provided updated summary effect estimates consistent with existing meta‐analyses on individual cancers, including significant associations with gastric cancer, 8 pancreatic cancer 7 and null associations for breast cancer, 16 liver cancer 17 and nasopharyngeal cancer 18 for some blood groups. Compared to prior studies this full‐scale investigation, featuring the extension of comparison models, cancer categorization and subgroup analysis by ethnicity, outlines an overall landscape of relationship between ABO blood group and cancers.…”
Section: Discussionmentioning
confidence: 61%
“…The authors found that regarding the overall survival (OS) for locally advanced NPC patients with high lymphocyte levels, compared to non-A subgroups, the A blood group patients had better rates. A meta-analysis by Shao-wu Jing showed that, in Chinese patients, blood group O was associated with a lower incidence of NPC, while group A had no correlation with NPC [ 41 ].…”
Section: Discussionmentioning
confidence: 99%